Synthesis design of UWB bandpass filter using multiple resonance resonator (MRR) - Khalid, S. (Institution of Engineering and Technology, 2014)
An ultra-wideband (UWB) bandpass filter synthesis and design, using a multiple resonance resonator (MRR), is presented. Mixed-mode coupling is used to introduce a finite transmission zero to increase the filter selectivity. The equivalent circuit of the design is used to find the filtering function using even-odd mode analysis. The synthesis procedure is done on an extracted filtering function in order to realise the quasi-Chebyshev filtering response. Finally, a compact filter prototype has been fabricated to validate the synthesis theory and simulated design. The measured and simulated results show good agreement. Â© The Institution of Engineering and Technology 2014.